Exploring effective English learning strategies for athlete students at a senior high school - Saputri, Maulidarni; Yulia, Yuyun; Nasution, Khairunnisa; Kusumawati, Riyani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study investigates the English learning strategies employed by athlete students at a senior high school in Kalasan, Yogyakarta, aiming to pinpoint the most effective approaches aligned with their learning preferences. Utilizing a quantitative research design, data were gathered through the Strategy Inventory for Language Learning (SILL) from 26 athlete students actively involved in diverse sports. The results indicate that cognitive strategies, employed by 76% of participants, emerged as the most prevalent, underscoring the students’ inclination toward practical, problem-solving activities. Social strategies, with a 73% usage rate, emphasized the value of collaboration, while affective strategies, at 63%, addressed emotional factors such as motivation and anxiety management. In contrast, compensatory (61%), metacognitive (61%), and memory (59%) strategies showed moderate to lower adoption, suggesting opportunities for further development. The findings highlight cognitive, social, and affective strategies as particularly effective for athlete students, offering practical guidance for educators to adapt teaching methods that balance the competing demands of academic achievement and athletic commitments.